The management of intracapsular hip fractures. Issue 2 (April 2016) - Winter, Alison; Bradman, Hannah; Fraser, Calum; Holt, Graeme
Abstract: Hip fractures are the most common, serious musculo-skeletal injury to affect the elderly population. Approximately 80 000 hip fractures occur each year in the UK with an estimated annual associated cost of £2 billion. The annual burden of hip fractures is expected to increase over the coming years as a result of demographic changes to the UK population. There is significant mortality and morbidity associated with these injuries. It is therefore essential that a multidisciplinary approach is employed to maximize potential recovery after this injury. The surgical management of hip fractures varies depending upon the anatomical location of the fracture. Approximately one half of all hip fractures are intracapsular in nature. In this article we explore the current controversies in treatment of these fractures and factors which may affect management decisions.